Structural variations and magnetic properties of the quantum antiferromagnets Cs2CuCl4-xBrx - Cong, P; Wolf, B; van Well, N; Haghighirad, A; Ritter, F; Assmus, W; Krellner, C; Lang, M (Institute of Electric and Electronic Engineers, 2014)
Depending on the crystal growth conditions, an orthorhombic (O-type) or a tetragonal (T-type) structure can be found in the solid solution Cs 2 CuCl 4-x Br x (0 ≤ x ≤ 4). Here, we present measurements of the temperature-dependent magnetic susceptibility and isothermal magnetization on the T-type compounds x = 1.6 and 1.8 and compare these results with the magnetic properties recently derived for the O-type variant. The systems were found to exhibit quite dissimilar magnetic properties, which can be assigned to differences in the Cu coordination in these two structural variants. Whereas the tetragonal compounds can be classified as quasi-2-D ferromagnets, characterized by ferromagnetic layers with a weak antiferromagnetic interlayer coupling, the orthorhombic materials, notably the border compounds x = 0 and 4, are model systems for frustrated 2-D Heisenberg antiferromagnets.